Images of sex and desire in Renaissance art and modern historiography
1 online resource
Keywords: "Studies on gender and sexuality have proliferated in the last decades, covering a wide spectrum of disciplines. This anthology offers a metanarrative of sexuality as it has been recently embedded in the art historical discourse of the European Renaissance. It revisits 'canonical' forms of visual culture, such as painting, sculpture and a number of emblematic manuscripts. The contributors focus on one image--either actual or thematic--and examine it against its historiographic assumptions. Through the use of interdisciplinary approaches, the essays propose to unmask the ideology(ies) of representation of sexuality and suggest a richer image of the ever-shifting identities of gender. The anthology focuses on the Italian Renaissance, but also includes case studies from Germany and France. "--Provided by publisher.